Influence of The Addition of Steel Chips on the Compression Resistance of Artisan Bricks in Masonry Prisms (LACCEI, 2024)
This research aims to determine the influence of the addition of steel shavings (VA) on the compressive strength of artisan bricks in masonry prisms, for which 30 prisms were made, each prism made up of three bricks and a 1.5 joint. cm, 6 of these for each percentage that was 0%, 5%, 10%, 15% and 20% addition of steel chips. The research is experimental and according to its nature it is quantitative. The results indicate that for an addition of 15% (V.A.), the compressive strength in brick units increases and is optimal, resulting in 74.31 kg/cm², unlike the standard brick, which is 54.33 kg/cm² In prisms the same thing happens for an addition of 15% (V.A.) the compressive strength reaches 49.30 kg/cm² unlike the standard prism which is 23.88 kg/cm², however, if the resistances are added to more than this percentage they start to go down. It was concluded that the influence of the addition of (V.A.) in handmade bricks and masonry prisms has a positive influence, improving this property by 206.44% with respect to the standard prisms, but up to 15% of addition of (V.A.)